Tuberculous adrenal abscess revealed by pleurisy: An extremely rare presentation: About a case - N. Bahlouli; A. Lemrabet; F. Chait; K. Sfaar; S. Essetti; L. Ihsane; O. El aoufir; L. Jroundi (Urology Case Reports)
We report an extremely rare presentation of a tuberculous adrenal abscess discovered accidently during a chest CT scan. This case involves a 21-year-old male patient with pleurisy and a left adrenal abscess simultaneously of tuberculous origin, without clinical or biological signs of adrenal insufficiency. The condition showed complete regression of the abscess after medical treatment. The aim of our work is to report an extremely rare case of adrenal tuberculosis in its abscessed form, to describe the imaging aspect in order to facilitate the diagnosis for radiologists.